2021
DOI: 10.2485/jhtb.30.323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacterial Infection on Bone Quality and Structure in Osteonecrosis of the Jaw by Bisphosphonate (BP) Administration

Abstract: Bisphosphonate (BP) formulations are drugs that improve bone strength by suppressing osteoclast activation, preventing fractures of the vertebrae and the femoral head, but their side effects include osteonecrosis of the jaw (ONJ). In this case it is known as medication-related osteonecrosis of the jaw (MRONJ), and pathological and microbiological investigations have suggested that infection is one major causative factor. However, many points regarding the etiology of ONJ and its causative factors remain uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…The second is local infection. In many animal studies, inflammation or infection of the jawbone causes MRONJ, similar to that observed in humans [ 8 - 15 ]. The presence of bacteria in necrotic bone in clinical specimens and the spread of necrotic bone with the severity of inflammation suggest that bacterial infection may be involved in the development and onset of MRONJ [ 14 - 17 ].…”
Section: Discussionmentioning
confidence: 65%
“…The second is local infection. In many animal studies, inflammation or infection of the jawbone causes MRONJ, similar to that observed in humans [ 8 - 15 ]. The presence of bacteria in necrotic bone in clinical specimens and the spread of necrotic bone with the severity of inflammation suggest that bacterial infection may be involved in the development and onset of MRONJ [ 14 - 17 ].…”
Section: Discussionmentioning
confidence: 65%